2006
DOI: 10.1001/archinte.166.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Excessive Anticoagulation With Phytonadione (Vitamin K)

Abstract: Background: : Patients taking oral anticoagulants with an international normalized ratio (INR) greater than 4.0 are at increased risk for bleeding. We performed a metaanalysis to determine the effectiveness of phytonadione (vitamin K) in treating excessive anticoagulation. Methods:The MEDLINE, EMBASE, and Cochrane Library databases were searched (without language restrictions) for articles published between January 1985 and September 2004. Randomized controlled trials or prospective, nonrandomized trials that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
(42 reference statements)
0
29
1
3
Order By: Relevance
“…9,10 A meta-analysis of vitamin K studies found that oral and intravenous vitamin K-treated patients achieved similar rates of target INR at 24 hours (82% vs 77%), but oral vitamin K resulted in a higher frequency of INR overcorrection (INR <1.5). 11 In our study, there was no difference between the intravenous and oral groups in bridging incidence or duration. Although there was a significantly higher duration of hospital stay in the intravenous group, the cause was unclear.…”
Section: Resultscontrasting
confidence: 46%
“…9,10 A meta-analysis of vitamin K studies found that oral and intravenous vitamin K-treated patients achieved similar rates of target INR at 24 hours (82% vs 77%), but oral vitamin K resulted in a higher frequency of INR overcorrection (INR <1.5). 11 In our study, there was no difference between the intravenous and oral groups in bridging incidence or duration. Although there was a significantly higher duration of hospital stay in the intravenous group, the cause was unclear.…”
Section: Resultscontrasting
confidence: 46%
“…The reversal of vitamin K antagonists can be monitored with the INR, which is very sensitive to factor VII levels. A recent meta-analysis of 21 studies (n=983) suggested that oral and intravenous vitamin K had similar efficacy, but that subcutaneous vitamin K was inferior and similar to placebo 14. In the four trials using oral vitamin K (n=75), the proportion of patients with a target INR at 24 hours was 82% (95% confidence interval 70% to 93%), which was similar to that with intravenous vitamin K (six trials, n=69; target INR 77%, 95% CI 60% to 95%) 14…”
Section: How Well Do They Work?mentioning
confidence: 99%
“…High doses of vitamin K1 can predispose to warfarin resistance for a week or more, rendering the patient at risk for thrombotic events [7]. Oral administration is more rapid, predictably effective, safer, and more convenient than administration by subcutaneous (SQ) and intramuscular (IM) routes [8][9][10][11][12][13][14]. When there is a greater urgency to reverse anticoagulation, Vitamin K1 can be administered by slow intravenous (IV) infusion [8,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…When there is a greater urgency to reverse anticoagulation, Vitamin K1 can be administered by slow intravenous (IV) infusion [8,15,16]. Vitamin K1 administered by the oral or IV routes lower INRs equivalently at 24 h [11,16].…”
Section: Introductionmentioning
confidence: 99%